A Review: Aesthetic element in prosthetic’s cosmetic design for lower limb physical amputees - Nor Rofizah Johari; Zamrudin Abdullah; Nurhikma Mat Yusof (Environment-Behaviour Proceedings Journal, 2025)
This systematic study aims to establish the key aesthetic elements in prosthetic cosmetic design. The increasing number of amputated individuals from congenital and traumatic causes implies the need for effective prosthetic design. It is crucial to note that most past research is not artistic and design-oriented. Therefore, utilizing the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), this study reviewed articles from 2018 to 2024; sourced from Google Scholar. The review found seven major clusters leading to several sub-themes. The author states some ideas for future studies at the end of this article.